The use of the VerifyNow P2Y12 point-of-care device to monitor platelet function across a range of P2Y12 inhibition levels following prasugrel and clopidogrel administration - Jakubowski, Joseph A; Payne, Christopher D; Li, Ying G; Brandt, John T; Small, David S; Farid, Nagy A; Salazar, Daniel E; Winters, Kenneth J (Thrombosis and haemostasis, 2008)
Variability in response to antiplatelet agents has prompted the development of point-of-care (POC) technology. In this study, we compared the VerifyNow P2Y12 (VN-P2Y12) POC device with light transmission aggregometry (LTA) in subjects switched directly from clopidogrel to prasugrel. Healthy subjects on aspirin were administered a clopidogrel 600 mg loading dose (LD) followed by a 75 mg/d maintenance dose (MD) for 10 days. Subjects were then switched to a prasugrel 60 mg LD and then 10 mg/d MD for 10 days (n = 16), or to a prasugrel 10 mg/d MD for 11 days (n = 19). Platelet function was measured by LTA and VN-P2Y12 at baseline and after dosing. Clopidogrel 600 mg LD/75 mg MD treatment led to a reduction in P2Y(12) reaction units (PRU) from baseline. A switch from clopidogrel MD to prasugrel 60 mg LD/10 mg MD produced an immediate decrease in PRU, while a switch to prasugrel 10 mg MD resulted in a more gradual decline. Consistent with the reduction in PRU, device-reported percent inhibition increased during both clopidogrel and prasugrel regimens. Inhibition of platelet aggregation as measured by LTA showed a very similar pattern to that found with VN-P2Y12 measurement, irrespective of treatment regimens. The dynamic range of VN-P2Y12 appeared to be narrower than that of LTA. With two different thienopyridines, the VN-P2Y12 device, within a somewhat more limited range, reflected the overall magnitude of change in aggregation response determined by LTA. The determination of the clinical utility of such POC devices will require their use in clinical outcome studies.